Development of an insurance industry image assessment index - O. I. Larina; N. V. Moryzhenkova (Вестник университета)
The article discusses the results of the study of consumer attitudes towards the insurance sector in the Russian Federation. A low level of financial literacy, cases of fraud by insurers lead to the formation of a negative image of the insurance industry, even if the respondents have a positive experience of using insurance products. In world practice the relationship between reputation management of companies and their financial condition has been proven, however, a quantitative assessment of the insurance sector image has been not carried out earlier. The article offers a methodology for assessing the insurance sector image? using the author’s index, and provides an example of its calculation based on the Russian insurance market. The developed indicator will allows to objectively assess the dynamics of consumer attitudes to insurance, and to conduct a cross-country comparison of the indicator.